The Effect of Financial Attitudes on Financial Behavior with Financial Self-Efficacy as a Mediating Variable - Khusaini, Imron Nur; Anwar, Muhadjir (East Asian Journal of Multidisciplinary Research, 2023)
Individuals need to manage and make decisions on their personal finances in order to meet their needs and have good financial behavior for good financial goals. Financial self-efficacy theory was studied to see the effect of financial attitudes on financial behavior. This study was conducted with the aim of: a) to determine the effect of financial attitudes on financial behavior in Management Students of UPN "Veteran" East Java; b) to determine the effect of Financial Self Efficacy on financial behavior in UPN "Veteran" East Java management students; c) to ascertain how Financial Self-Efficacy can act as a mediator between financial attitudes and financial behavior in UPN "Veteran" East Java management students.In this study, a Likert scale is used as a measurement tool in a quantitative approach method. This research technique is Partial Least Square (PLS). The sample was taken by random sampling technique with the number of samples determined by the slovin formula with an error rate of 10%. Data information used in the study, namely primary data and secondary data obtained from first sources specifically collected through questionnaires. The population of this study was 1639 UPN Veteran East Java Management Students from batches 2019 to 2022.